2003
DOI: 10.1080/0014013031000121598
|View full text |Cite
|
Sign up to set email alerts
|

No interference of task complexity with circadian rhythmicity in a constant routine protocol

Abstract: Time course in task performance has been studied extensively. In particular, the investigation of circadian rhythmicity in task performance that varied in complexity. However, these studies disclosed heterogeneous outcomes. This could be the result of confounding exogenous factors, the use of diverse tasks, as well as accumulating sleepiness interfering with the underlying circadian drive. The present study varied task demands systematically within a single task and a dual task, using a constant routine protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
4
15
1
Order By: Relevance
“…Similar results were observed in previous studies with simple tracking tasks measuring visual-motor skills (Buck 1977;Dorrian et al 2000;Mullaney et al 1983;Goh et al 2001;van Eekelen & Kerkhof 2003). It is also possible that the failure to adjust to the changes in the task during the morning hours also affected the efficiency with regard to responding to the 8th-20th stimuli, as no reduction in the response to the first stimulus after a change was observed during early morning, which also depends on visual-motor skills.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results were observed in previous studies with simple tracking tasks measuring visual-motor skills (Buck 1977;Dorrian et al 2000;Mullaney et al 1983;Goh et al 2001;van Eekelen & Kerkhof 2003). It is also possible that the failure to adjust to the changes in the task during the morning hours also affected the efficiency with regard to responding to the 8th-20th stimuli, as no reduction in the response to the first stimulus after a change was observed during early morning, which also depends on visual-motor skills.…”
Section: Discussionsupporting
confidence: 84%
“…This revealed that late sleepers' timing was more stable in the evening than in the morning, whereas early sleepers exhibited no difference between the two recordings. Our result can therefore be added to a growing list of aspects of human performance that are subject to circadian fluctuations (Kleitman et al, 1938; Atkinson et al, 1993; Coldwells et al, 1994; Gauthier et al, 1996; Monk and Kupfer, 2000; Dosseville et al, 2002; Van Eekelen and Kerkhof, 2003). In our context, it is interesting to notice that even long-term, massed practice of these expert musicians has not been able to wash out circadian fluctuations in performance.…”
Section: Discussionmentioning
confidence: 90%
“…Circadian fluctuations are evident in various physiological functions of the human organism: clinical chemical parameters and endocrinological parameters such as concentration of hemoglobin, potassium, iron, adrenaline, noradrenaline, cortisol, and other hormones in blood and serum (Wisser and Breuer, 1981), body temperature (Aschoff, 1955) as well as cognitive functions such as reaction time to sensory cues (Kleitman et al, 1938) and memory tasks of various complexity (Van Eekelen and Kerkhof, 2003). In particular, circadian fluctuations also occur within the sensorimotor system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circadian variations have been found in tasks which measure executive functions without specifying the components involved, for example, complex labyrinths, 32 or in a dual task 33 . However, it is necessary to identify circadian rhythms in each one of the components of executive functions.…”
Section: Introductionmentioning
confidence: 99%